Copper-Induced Synthesis of Ascorbate, Glutathione and Phytochelatins in the Marine Alga Ulva Compressa (Chlorophyta) - Moenne-Munoz, A; Dennett-Rios, G; Contreras-Arredondo, R; Gonzalez-Figueroa, A (2012)
In order to analyze the synthesis of antioxidant and heavy metal-chelating compounds in response to copper stress, the marine alga Ulva compressa (Chlorophyta) was exposed to 10 ?M copper for 7 days and treated with inhibitors of ASC synthesis, lycorine, and GSH synthesis, buthionine sulfoximine (BSO). The levels of ascorbate, in its reduced (ASC) and oxidized (DHA) forms, glutathione, in its reduced (GSH) and oxidized (GSSG) forms, and phytochelatins (PCs) were determined as well as activities of enzymes involved in ASC synthesis, l-galactose dehydrogenase (GDH) and l-galactono 1,4 lactone dehydrogenase (GLDH), and in GSH synthesis, ?-glutamylcysteine synthase (?-GCS) and glutathione synthase (GS). The level of ASC rapidly decreased to reach a minimum at day 1 that remained low until day 7, DHA decreased until day 1 but slowly increased up to day 7 and its accumulation was inhibited by lycorine. In addition, GSH level increased to reach a maximal level at day 5 and GSSG increased up to day 7 and their accumulation was inhibited by BSO. Activities of GDH and GLDH increased until day 7 and GLDH was inhibited by lycorine. Moreover, activities of ?-GCS and GS increased until day 7 and ?-GCS was inhibited by BSO. Furthermore, PC2, PC3 and PC4, increased until day 7 and their accumulation was inhibited by BSO. Thus, copper induced the synthesis of ascorbate, glutathione and PCs in U. compressa suggesting that these compounds are involved in copper tolerance. Interestingly, U. compressa is, until now, the only ulvophyte showing ASC, GSH and PCs synthesis in response to copper excess. © 2011 Elsevier Masson SAS.
Keywords: Ascorbate; Copper; Glutathione; Marine alga; Phytochelatins; Ulva compressa